1999
DOI: 10.1007/bf02433421
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcal IgG Fc-binding proteins are factors initiating experimental glomerulonephritis

Abstract: Immunomorphological analysis of renal tissue from rabbits immunized with group A streptococci differing in the expression of IgG Fc-binding proteins showed that only IgG Fc-positive streptococci induced destructive degenerative changes in the kidneys classified as membranous proliferative glomerulonephritis with symptoms of fibroplastic glomerulonephritis. These morphological changes in renal tissue are comparable to changes in patients with acute poststreptococcal glomerulonephritis. Depositions of IgG and C3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…Similar to post-streptococcal glomerulonephritis, the serum C3 level of SGN patients displayed a dynamic change. Some studies have suggested that S. scabiei infections lead to the local deposition of C3 in the skin, which induces a strong inflammatory response [18,19,21]. This deposition of C3 in the skin probably explains, in part, the decreased C3 level in the early stage of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to post-streptococcal glomerulonephritis, the serum C3 level of SGN patients displayed a dynamic change. Some studies have suggested that S. scabiei infections lead to the local deposition of C3 in the skin, which induces a strong inflammatory response [18,19,21]. This deposition of C3 in the skin probably explains, in part, the decreased C3 level in the early stage of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Though whole antibodies (e.g., IgGs, Figure ) have been previously employed in a number of biodiagnostic applications to interface superparamagnetic nanoparticles (SPNs) to bacteria, antibodies have an inherent cross-reactivity associated with them because the Fc region is common to different antibodies and can interact with multiple targets despite the fact that their variable region (F V ) is unique. For example, Ho et al recently demonstrated that IgG-based nanoparticles interact with protein A (a surface protein unique to Staphylococcus aureus ) as well as other surface markers such as protein M present on the surface of other bacteria ,, . To avoid the cross-reactivity problems associated with traditional antibodies, smaller, single-chain variable fragments (scFv) lacking the Fc region can be utilized (Figure ), but these fragments are frequently unstable and prone to aggregation.…”
Section: Introductionmentioning
confidence: 99%
“…Несмотря на то что ПСГН считается одним из наиболее изученных поражений почек, данные о патогенезе этого заболевания являются недостаточными. Исследуются и обсуждаются несколько патогенетических теорий, которые включают в себя синтез противопочечных анти-тел, иммуннокомплексное воспаление, а также воздействие на клубочки почек цистеиновой протеазы (SPE B) БГСА [17][18][19].…”
unclassified